IDENTIFIKASI BAHAYA DAN ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA INSTALASI PENGOLAHAN AIR DI PERUMDA TIRTA PENGABUAN: Hazard Identification and Risk Analysis of Occupational Safety and Health at Water Treatment Plants at Perumda Tirta Pengabuan - Dwi Mulyo, Nanda; Halim, Rd.; Mawarti Perdana, Silvia (Poltekes Kemenkes Tanjungpinang, 2022)
Water treatment installation is a part that moves in the water treatment process which of course has various problems that exist related to the occurrence of an accident or occupational disease in the process. Therefore, it is necessary to identify hazards, risk assessments, risk analysis, and recommend controls to prevent the occurrence of things that can cause work accidents and occupational diseases. The purpose of this study is to find out what hazards can potentially cause work accidents and occupational diseases at the Water Treatment Plant at Perumda Tirta Pengabuan. The type of research used in this research is descriptive qualitative research with observation and interview methods. The informants in this study were 8 respondents from the Water Treatment Plant. Then the results would be analyzed qualitatively, namely reduction, display, and conclusion. Indicates that the Water Treatment Plant has implemented the K3 program but has not been fully implemented. Through the identification of hazards in 10 activities, several types of hazards were found, namely, physical or mechanical hazards, chemical hazards, biological hazards, and ergonomic hazards. Furthermore, the identified hazards are grouped into high, medium, and low risks. It is necessary to add personal protective equipment, make repairs to parts that pose a risk of danger, as well as conduct counseling and training for workers at the Water Treatment Plant.